Phosphorus removal in ponds - Surampalli, Rao Y.; Banerji, Shankha K.; Pycha, Charles J.; Lopez, Ernesto R. (Water science and technology, 1995)
The municipal lagoon treatment systems which remove phosphorus by chemical addition are the subject of this special study. The objectives of this study were to determine the degree of success of lagoon treatment systems in removing phosphorus and to identify any operational problems. In order to obtain basic data for this study, thirty-two lagoon treatment systems in Michigan and Minnesota were investigated. Chemicals typically used for phosphorus removal include metal salts such as aluminium sulfate (alum), ferrous and ferric chloride, lime, and various polymers. The overall experience with these lagoon systems is that the technology, in its various configurations, has been working very well. Of the thirty-two lagoon treatment facilities reviewed, only two facilities were having problems meeting consistently the effluent phosphorus limits. Generally, the permitted effluent phosphorus limit is 1 mg/l. The influent phosphorus concentrations varied between 0.5 and 15 mg/l. Alum and ferric chloride applications produced consistently high quality effluents while lime applications were not as effective in removing phosphorus. None of these lagoon treatment systems experienced problems with build-up of sludges to levels which affected the effluent concentrations. Accumulated amounts were an inch or less per year, consistent with solids build-up in the primary lagoon cells.